Explaining forest productivity using tree functional traits and phylogenetic information: two sides of the same coin over evolutionary scale?. Issue 9 (27th March 2015) - Paquette, Alain; Joly, Simon; Messier, Christian
Abstract : The importance of biodiversity for ecosystem functioning and for the provisioning of services to humanity is well established. Yet we still are looking for methods to quantify this biodiversity that are both relevant and efficient. Here we show that phylogenetic information can help, especially when key functional traits are unavailable, and how it relates to functional traits of species. Abstract: Given evidences that diverse ecosystems provide more services than depauperate ones, much attention has now turned toward finding meaningful and operational diversity indices. We ask two questions: (1) Does phylogenetic diversity contain additional information not explained by functional traits? And (2) What are the strength and nature of the correlation between phylogeny and functional traits according to the evolutionary scale considered? We used data from permanent forest plots of northeastern Canada for which these links have been demonstrated and important functional traits identified. We show that the nature of the relationship between traits and phylogeny varies dramatically among traits, but also according to the evolutionary distance considered. The demonstration that different characters show phylogenetic autocorrelation at different evolutionary depths suggests that phylogenetic content of traits may be too crude to determine whether phylogenies contain relevant information. However, our study provides support for the use of phylogenies to assess ecosystem functioning when key functional traits are unavailable. We also highlight a potentially important contribution of phylogenetics for conservation and the study of the impact of biodiversity loss on ecosystem functioning and the provision of services, given the accumulating evidence that mechanisms promoting diversity effects shift over time to involve different traits.